Pengaruh Metode Pembelajaran Contextual Teaching and Learning terhadap Motivasi Belajar Pendidikan Agama Islam Siswa Kelas V SDN 1 Lando - Hendra; Firly Nazilah Putri; M.Siratul Khaeri (Indonesian Journal of Action Research, 2026)
Purpose – The learning motivation of students in Islamic Religious Education at SDN 1 Lando is relatively low, mainly due to the lack of variation in teaching methods used during the learning process. The purpose of this study is to determine whether there is an influence of the Contextual Teaching and Learning method on the learning motivation of fifth-grade students in Islamic Religious Education at SDN 1 Lando in the 2024/2025 academic year. Design/methods –This research applied a quantitative method using a quasi-experimental approach with a Nonequivalent Control Group Design. Two groups were involved: an experimental group (Class V-A, 30 students) that received treatment using the CTL method, and a control group (Class V-B, 30 students) taught using conventional methods. The sample was selected through purposive sampling. Findings – The findings reveal that the implementation of the ctl method positively and significantly affects students’ learning motivation in Islamic Religious Education at SDN 1 Lando in the 2024/2025. The pretest value of 68.00 and the posttest value of 78.50 indicate that the application of the CTL method has a significant impact on increasing student learning motivation. This is also proven through the results of a simple linear regression test which shows a significance level value of 0.000 <0.05 and a calculated t of 7.265> t table 2.048, and the coefficient of determination R² = 0.652 indicates that the CTL method contributes 65.2% to increasing the motivation to learn Islamic Religious Education of fifth-grade students at SDN 1 Lando.